Fundamental of Entrepreneurship ENT300 : Cafe & Jamm's / Siti Nurfaizah Isyak ... [et al.] - Isyak, Siti Nurfaizah; Asong, Katerina; Khairil Amri, Ulul Azmi; Adenan, Ishak; Hanif, Noor Aida (2013)
Café & Jamm's was proposed to be launched on July,2013 Our vision to continue to support and work in the underground music label,while continuously growing with it. The standard today calls for chill and relax jamming studio.Meanwhile,its mission is to provide a leisure jamming studio and café services to youngster and musicians at the underground level. Whether they are new to the qrt of jamming or like the feel and mechanics of a fundamental system,this studio is here to aid in their musical needs-Our business and its supporters strive to deliver an end result that brings satisfaction and pride to the people that jamming here-Our company objectives is to gain as much as sales and profit within the first 3 years of our establishment so that we can predict where and what is our strength to continue doing this business ahead.Our business is located nearby UNIMAS,Banks,Taman Desa 11mu and Summer Shopping Mall (under construction).